Self-aggregation of hydrophobically modified dextrin and their interaction with surfactant - Bai, Guangyue (2008)
A series of newly hydrophobically modified polymers (dexC16) with different degrees of substitution (DSC16) have been synthesized. They can self-assemble to form micelle-like aggregates through association of the hydrophobic alkyl chains in aqueous solution. The self-aggregation processes, i.e. the critical micelle concentrations (cmc's) of the polymers were characterized by steady-state fluorescence. Further, the interaction between these dexC16 polymers and ionic surfactants (SOS, SDS and DTAC) was investigated by isothermal titration calorimetry (ITC). For the studied mixed systems some important parameters can be derived from calorimetric titration curves, such as interaction enthalpies, critical concentrations and enthalpies of aggregation. The critical concentrations and the aggregation behaviour for the dexC16/SDS system were confirmed by fluorescence measurements. The effects of hydrophobic side group concentrations on the interaction were evaluated in detail. Importantly, we show that the aggregation behaviour of the mixed systems depends on the molar ratio of surfactant to hydrophobic side group (R = ns/nside group).